PENGARUH DISIPLIN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN DI PT SANKEI GOHSYU INDUSTRIES - Karyono Karyono (LP2M Universitas Bina Bangsa, 2021)
This study aims to determine the influence of work discipline on performance, the influence of work stress on employee performance and to know the influence of work discipline and work stress simultaneously on the performance of employees of PT Sankei Gohsyu Industries. The type of research used is quantitative research. The population in this study was 89 people. The sample used as many as 89 respondents at PT Sankei Gohsyu Industries with saturated sampling method. The method of data collection used is questionnaire as the main data collection tool. The data was analyzed with multiple linear regressions with the help of SPSS version 22 software. The results showed that work discipline (X1) had a partial significant effect on employee performance (Y). The value of positive t count, meaning that the more improved the work discipline, the more the employee performance increases, the variable work stress (X2) does not partially affect the performance of employees (Y) and work discipline (X1) and work stress (X2) together - equally significant affect the performance of employees (Y) but the value of coefficient interachievement is very low at 17.0%. Therefore, to improve employee performance required work discipline, because the work discipline variable (X1) is the variable that has the most dominant effect on the performance variable